2018
DOI: 10.1096/fj.201700923r
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of KLF12 by microRNA‐20b and microRNA‐106a in cystogenesis

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is one of the most common inherited disorders. ADPKD is caused by mutations in the gene encoding either polycystic kidney disease 1 ( PKD1) or polycystic kidney disease 2 ( PKD2). Patients with ADPKD show progressive growth of cystic fluid-filled renal cysts. Here, we used Pkd2 control mice and Pkd2:HoxB7-Cre experimental mice, which are bred to have a conditional deletion of Pkd2 in the collecting ducts, and analyzed the expression pattern of microRNAs (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…We suggested that this difference may be related to their phenotypic differences. Furthermore, we observed decreased expression of miR-20b-5p and miR-106a-5p and up-regulation of its target KLF12 in Pkd2 f/f :HoxB7-Cre mice compared with Pkd2 f/f control mice (41). In addition, these findings were highly similar in a human cell line, mouse cell lines, and Pkd2 KO mouse embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
“…We suggested that this difference may be related to their phenotypic differences. Furthermore, we observed decreased expression of miR-20b-5p and miR-106a-5p and up-regulation of its target KLF12 in Pkd2 f/f :HoxB7-Cre mice compared with Pkd2 f/f control mice (41). In addition, these findings were highly similar in a human cell line, mouse cell lines, and Pkd2 KO mouse embryonic fibroblasts.…”
Section: Discussionsupporting
confidence: 65%
“…Conversely, downregulation of KLF12 resulted in a proliferative defect in multiple cancer cell lines (19,23,(44)(45)(46)(47). These observations were recapitulated in primary human cancer cells and mouse kidney cells (48,49). In this study, we observed a proliferative defect in KLF12-deficient NK cells in a competitive setting in BM chimeric mice upon Ag-and cytokine-mediated proliferation.…”
Section: Discussionsupporting
confidence: 60%
“…Outside of the miR-17–92 cluster, several other miRNAs have been associated with PKD. These include miR-21 [61], miR-20b-5p and miR-106a-5p [62], miR-199a-5p [63] and miR-501-5p [64] and suggest that targeting miRNAs pharmacologically may represent a new paradigm in PKD treatment [50].…”
Section: Molecular Targets On the Horizonmentioning
confidence: 99%